The Influence of Credit Risk on Company Earnings Management (Empirical Study of Banking Companies Listed on the IDX) - Putri Gatria Raisha Ariani; Rini Indriani; Fherza Azh Zahra (UNIVED Press, 2024)
This research aims to determine the effect of credit risk on earnings management in banking companies listed on the Indonesia Stock Exchange in 2019-2022. This research uses descriptive statistical analysis and multiple regression analysis using SPSS. The research data comes from annual financial reports obtained from the BEI website and the company's official website. Sample selection used purposive sampling technique so that 42 companies were obtained for a period of 4 years, but there were outlier data so that the total sample was 80 data. This research shows that credit risk as proxied by Gross NPL and Net NPL simultaneously influences earnings management in banking companies listed on the Indonesia Stock Exchange in 2019-2022.